MENAKAR KEBERMAKNAAN PEMBELAJARAN SAINS MENGGUNAKAN LEP MODEL - Tomo Djudin (Ikatan Keluarga Alumni FKIP Universitas Tanjungpura, 2014)
Teachers’ understanding on the nature of science will determine types of students learning activities in the schools. In designing a science teaching-learning process meaningfully, a teacher should consider and pay attention to the learning activities. They are (1) logical plane activities; (2) evidental or experiental plane activities; (3) psychological plane activities. A science text-books centered teaching should be modified because, the students comprehension about science products (concept and principles) could not be developed meaningfully by using text-books only. This culture is also contrary to the nature of science and is not able to build a science and technology literate people.